The liberal state and aid to the population in times of pandemic - Lopes Silveira, Phillipe; Leitão, Rômulo Guilherme (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
This article seeks to examine the role of the Liberal State during periods of emergency, especially in the face of the pandemic crisis of covid-19, a disease caused by the coronavirus, or, specifically, by SARS-CoV-2.In this context, the analysis permeates several currents of liberal thought, from libertarian authors who, in the philosophical line of Murray N. Rothbard, claim that state power is unproductive and immoral, to classics who understand the State as an essential entity for the protection of life, of freedom and property, like Frédéric Bastiat, reaching more modern liberal scholars, such as Ludwig von Mises, Friedrich Hayek and Milton Friedman, who, despite differing in relation to the intensity and mode of state intervention, develop their studies with a focus on in the indispensability of the State in relation to the institutional purposes for which it was created. In a second moment, according to the lessons of Stephen Holmes and Cass Sunstein, there is a need for public funding, through taxation, for the Liberal Fiscal State to act in order to guarantee rights of a liberal nature, even if these, paradoxically, whether what part of the doctrine treats as rights that require the state's duty of abstention. At the end, the possibilities of action of this model of State in pandemic periods are investigated, concluding that the State has fundamental relevance for the social and economic confrontation of the crisis established from the global spread of covid-19. The methodology uses bibliographic research, with consultations to books, national and foreign scientific articles and electronic sites specialized in legal, economic and political matters.